Music as a developer - Finley, Mary (My University, 1898)
Introduction: “When music, heavenly maid, was young; while yet in early Greece she sing;” She, divine daughter of joy, was yet - garmented in mystery – a being supernatural – regarded with superstition and fear. In many ways, this mystery of the past adds charm to the music of the present. More intensely interesting become the study of its history, and more forcibly do we realize it as that factor in our development which is so rapidly assuming such an important place in curriculum of life. Out of the darkness of the past, has come this ray of sunshine – the most effectual factor in bringing forth the highest and noblest powers of mind and soul.
Citation: Finley, Mary. Music as a developer. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Music; History; Greece; Development; Theses; Manuscripts (documents)